Dostosowanie prawa wewnętrznego w Republice Czeskiej do unijnych wymogów antydyskryminacyjnych na przykładzie prawa pracy - Matlochová, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article deals with one of the most crucial fields of EU social policy, namely with the principle of non-discrimination and its transposition into Czech national law. The degree of implementation varies greatly between the countries. The purpose of this article is to present the example of law implementation in the EU and highlight some specific issues of concern relating to the state of the adoption of EU anti-discrimination directives.
Keywords: wdrażanie prawa UE; dyskryminacja; czeskie prawo krajowe; prawo pracy; Trybunał Sprawiedliwości